2004
DOI: 10.1080/15287390490491909
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Microbiological Risks of Drinking Water

Abstract: The microbiological contamination of drinking water supplies can have serious health consequences for consumers, and this has been dramatically illustrated in recent years by two disease outbreaks in Canada. In this paper, some factors that can influence the microbiological quality of drinking water and its management are examined. Frameworks have been proposed that help to clarify the main elements of health risk assessment and risk management, and, in accordance with these, risks can be logically characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…population growth, synthetic chemical use and industrialization) continue to put increased pressures on water quality and quantity in Canada (Murdoch et al 2000;Carr & Neary 2008). Internationally, there have been efforts to understand the characteristics of individuals at risk and water consumption levels (Westrell et al 2006;Mons et al 2007;Kyunghee et al 2009) as these pressures have the potential to increase the susceptibility of drinking water to contamination from chemicals and microorganisms (Hunter et al 2003;Charron et al 2004;Krewski et al 2004; Thomas et al 2006). Throughout the world, contaminated water continues to be a cause of endemic and epidemic gastrointestinal illness (Craun et al 1998;WHO doi: 10.2166WHO doi: 10.…”
Section: Introductionmentioning
confidence: 98%
“…population growth, synthetic chemical use and industrialization) continue to put increased pressures on water quality and quantity in Canada (Murdoch et al 2000;Carr & Neary 2008). Internationally, there have been efforts to understand the characteristics of individuals at risk and water consumption levels (Westrell et al 2006;Mons et al 2007;Kyunghee et al 2009) as these pressures have the potential to increase the susceptibility of drinking water to contamination from chemicals and microorganisms (Hunter et al 2003;Charron et al 2004;Krewski et al 2004; Thomas et al 2006). Throughout the world, contaminated water continues to be a cause of endemic and epidemic gastrointestinal illness (Craun et al 1998;WHO doi: 10.2166WHO doi: 10.…”
Section: Introductionmentioning
confidence: 98%
“…Taken together, our findings will help guide future studies assessing the utility of screening and follow-up of patients who recover from acute bacterial gastroenteritis. More importantly, maintaining safe drinking water remains essential to human health, [36][37][38][39][40] as transient bacterial contaminations may have implications well beyond a period of acute self-limited illness. 41 …”
Section: Discussionmentioning
confidence: 99%
“…An investigation revealed that the outbreak could have been prevented if free chlorine in the water supply was monitored daily. In the second case, that for North Battleford, more than 7,000 people became ill due to the contamination of drinking water by Cryptosporidium parvum (Krewski, et al 2004). Numerous other events have been reported (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…E.coli) can be used to indicate the presence of other bacterial pathogens, but are less effective at predicting risk from protozoa and viruses (Payment, 1999). Further, in any type of monitoring system that involves, a delay between the time of sample collection and the time when the results are obtained, contaminated water may be distributed to the consumers before there is knowledge of any danger (Krewski, et al 2004). This is an especially important issue in pathogen detection, where many of the current detection/identification procedures require days for identification of an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation